Farmland values and bidder behaviour in first-price land auctions. (13th May 2019) - Croonenbroeck, Carsten; Odening, Martin; Hüttel, Silke
Abstract: We investigate potential asymmetries among bidders in land auctions that may entail market inefficiencies. Using representative data for eastern Germany including winning bids, bidder characteristics and land amenities, we pursue a structural approach to derive distributions of latent land values for different bidder groups. By applying non-parametric techniques, we cannot find evidence for distinct asymmetries while differentiating between legal entities, tenancy status and nationality of bidders. Our findings challenge the hypothesis that land privatisation via auctions discriminates against certain buyer groups – an argument that is often used to justify stricter regulation of agricultural land markets.